The curative role of bitumen in traditional Persian medicine - Shahriari, Mahdi (Array, 2018)
Aim: Bitumen is a natural substance effusing from rocks’ notches in some highland areas; it has been known as an effective remedy for treating some illnesses. Considering pain relieving properties of bitumen in traditional Persian medicine (TPM) sources, this study aims to review the viewpoints of TPM sages regarding bitumen in the context of traditional Persian medicine. It also provides applicable information for interested researchers to conduct well-designed clinical trials and evaluate therapeutic effects of bitumen claimed in TPM sources. Material and method: Various databases including Embase, SID, IRANDOC, IranMedex, Scopus and PubMed were searched with keywords “bitumen” and “Shilajit”. Furthermore, main traditional Persian medicine sources including Avicenna’s “Canon of medicine”, “Continens Liber” by Razes, “The storehouse of medicaments” by Aghili, “Gift for the faithful” by Momen Tonekaboni and “Measure for medicine” written by Muhammad Akbar Shah Arzani were reviewed with Persian keywords “Moomiaii” and “Mumnaei” Results: According to TPM sources, bitumen was used by Iranian’s physicians to treat a wide range of diseases. It was known especially as an effective remedy to improve gastrointestinal digestive problems. Conclusion: Bitumen is cited in traditional Persian medicine sources as an effective remedy for treatment of a wide range of diseases, especially GI disorders and bone pain. Recent studies showed the beneficial effects of bitumen in treatment of wound healing, however using it in medical practice for other health dilemma should be confirmed by conducting well-designed clinical studies in the future.